The Genealogy of the Kyrgys from Eylig-Khem (Tuva) - Oydup , Choyganmaa K. (The New Research of Tuva, 2021)
The life of Tuvan clans in the 20th century underwent significant changes: sedentarization, relocations, changes in the personal data of people due to the passportization of the 1940s, losses of relatives. The current desire of the Tuvans to restore family trees causes many problems with collection of data on people. This is shown by the example of the history of an ancestry — the Kyrgys from Eylig-Khem in the Ulug-Khem district of Tuva. The author of the article, a representative of this family, restores their history. The information was taken from the stories told by the author’s parents, childhood memories, and messages from her sisters — the full elder one, Lydia Kyrgysovna Budup (born in 1943), and the kindred sister (from the father’s side), Valentina Odurekovna Domur-ool (born in 1943). The article describes the life history of the author’s parents, Sedivaa Satovna Shagdyr (1918–1988) and Kyrgys Budupovich Shagdyr (1915–1987); family histories of khan-tѳrel — the kindred people — are presented. The author notes how many children, grandchildren and great-grandchildren there are in the family where they dwell today. The family tree that we have managed to compile is presented. Representatives of the kinship group today try not to lose touch with each other, they meet at the family dagylga (consecration rites) in the places where their ancestors lived in the Ulug-Khem district.